2015
DOI: 10.1007/s00520-015-2981-5
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer survivors’ perceptions of survivorship care follow-up options: a cross-sectional, mixed-methods survey

Abstract: WDTC survivors want specialists involved in their follow-up. A specialist/primary care shared-care approach appears to be a suitable alternative to specialist-led follow-up for TC survivors. Internet-based visits could address some aspects of follow-up care for some WDTC survivors. Future work should examine patient and provider requirements for shared, multi-modal survivorship care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…In line with previous research, the highest proportion of the survivors reported a preference for the medical specialist [14][15][16][17]. Previous research shows that survivors rate follow-up care provided by oncology nurses higher than follow-up care provided by general practitioners [16,17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with previous research, the highest proportion of the survivors reported a preference for the medical specialist [14][15][16][17]. Previous research shows that survivors rate follow-up care provided by oncology nurses higher than follow-up care provided by general practitioners [16,17].…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, few quantitative studies have assessed cancer survivors' preferences for follow-up care [14][15][16][17]. However, these quantitative studies neither identify survivorrelated characteristics associated with survivors' preferences for follow-up care nor describe the preferred care provider to discuss cancer-related problems.…”
mentioning
confidence: 99%
“…First, the majority of cancer patients report using the Internet as a source of health information. For example, 86% of a sample of 202 thyroid cancer patients [38] surveyed from the same hospital where this study was conducted, and 68% of a sample of 824 Canadian prostate cancer patients [39], reported using the Internet to search for information related to their cancer. As people spend more time online, they leave a digital trail.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up of patients with thyroid cancer is crucial both due to the life-long levothyroxine treatment and the remaining recurrence risk decades after the diagnosis. Follow-up options are studied with open ended questions, and the important factor for patients is the reassurance that the method of follow-up, whether it is primary care or specialised care, provides adequate care 207 .…”
Section: Hrqol Evaluated With Qualitative Methodsmentioning
confidence: 99%